Ramadan Excellent Merits and Virtuous Deeds - Salahuddin Yousaf, Hafiz; Translated into English by Siddheeque M.A Veliankodi (Lahore Darussalam, 1999)
How will you welcome the blessed month of Ramadan?Will Ramadan be the same as any other month of the year?What are some of the important deeds that one can do to acquire the most benefit from this blessed month?From the practice of the Prophet Muhammad (pbuh) - his kindness, Night Prayer (Traweeh) and I'tikaf - this book will help enlighten all of us.
Keywords: Fasts and feasts--Islam